Tabularność wiersza wolnego i jej konsekwencje lekturowe - Skibski, Krzysztof (Wydawnictwo „Poznańskie Studia Polonistyczne” i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
This article touches upon the tabular nature of free verse; here it indicates the individuality of verses in the text structure resulting from its non-linear character (spatiality) as a result of free verse. In other words, any text written in free verse is potentially a structure of coincidental syntax e.g. as a result of maximised equivalence each single verse is semantically independent and primarily independent with respect to syntax from the other verses. This article relies on the assumption that reception of a text written in free verse is non-linear and therefore tabular. This assumption is based on a conviction that the tabular nature is not a revelation of the new media or the change in perceiving texts propagated in the new media. Rather, it is a phenomenon typical of poetry; it started to accompany poetry when the notion of free verse was introduced. The text is illustrated with examples of poems by contemporary Polish authors.
The tabular nature of free verse and consequences to the reading process
Keywords: free verse; literary communication; tabular nature; poetic syntax; versification